Kr̥ṣṇadatta Pālīvāla racanā-sañcayana - Pālīvāla, Kṛṣṇadatta,Pālīvāla, Rītārānī (Sāhitya Akādemī, 2023)
Selected writings a modern Hindi author, on Hindi literature.
Keywords: Hindi literature; History and criticism.